2000
DOI: 10.1037/0278-6133.19.2.146
|View full text |Cite
|
Sign up to set email alerts
|

Perceptual style and behavioral pattern of individuals with functional gastrointestinal disorders.

Abstract: The present research examined the perceptual style and coping pattern characterizing individuals with functional gastrointestinal disorders. A matched case-control design was adopted to compare differences among the target group of individuals with functional gastrointestinal disorders (n = 40), a pain control group of individuals with rheumatism (n = 40), and the community control group of healthy individuals (n = 40). Perceptual style was measured by both monitoring and blunting responses to hypothetical str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
50
0
7

Year Published

2001
2001
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 42 publications
4
50
0
7
Order By: Relevance
“…The discriminative facility score ranges from 0 to 64, with a higher score indicates a greater extent of discriminative facility. The EMBSS (eight situations) has good internal consistency in a previous study (Cheng et al, 2000) and in the present study (α = .81 for the monitoring subscale and α = .78 for the blunting subscale). This scale also displays good criterion validity (Cheng, in press).…”
Section: Methodssupporting
confidence: 78%
“…The discriminative facility score ranges from 0 to 64, with a higher score indicates a greater extent of discriminative facility. The EMBSS (eight situations) has good internal consistency in a previous study (Cheng et al, 2000) and in the present study (α = .81 for the monitoring subscale and α = .78 for the blunting subscale). This scale also displays good criterion validity (Cheng, in press).…”
Section: Methodssupporting
confidence: 78%
“…64 Alternatively, IBS patients who are more distressed may seek any treatment possible to alleviate their condition, 18 engaging in potentially risky illness behaviors in an attempt to solve a seemingly unsolvable problem. 65 Finally, patients who recently saw a therapist reported significantly less perceived stigma from both personal relationships and from healthcare providers. There is wide and growing support for the use of behavioral therapies in the treatment of IBS.…”
Section: Discussionmentioning
confidence: 97%
“…Feelings of alienation, social withdrawal, and discrimination (especially from healthcare providers), may draw a person to a more holistic approach regardless of documented efficacy . Alternatively, IBS patients who are more distressed may seek any treatment possible to alleviate their condition, engaging in potentially risky illness behaviors in an attempt to solve a seemingly unsolvable problem . Finally, patients who recently saw a therapist reported significantly less perceived stigma from both personal relationships and from healthcare providers.…”
Section: Discussionmentioning
confidence: 99%
“…Although anxiety is believed to precede IBS symptoms most of the time (Sykes et al, 2003), it is also likely that anxiety may also be directed at physical symptoms once they occur. IBS patients and chronic worriers tend to devote higher levels of attentional resources toward monitoring threatening information (Butler & Matthews, 1983;Cheng, Hui, & Lam, 2000;Russel & Davey, 1993), and tend to perceive themselves as more vulnerable to disease (Crane & Martin, 2002). An interesting study looking at the relation between perceptual style and behaviors among IBS patients, patients with rheumatism, and healthy controls revealed that the patients with functional GI disorders had a tendency to appraise stressors as uncontrollable despite their objective controllability (Cheng et al, 2000).…”
mentioning
confidence: 99%